(untitled) (Research, Society and Development, 2020)
Buildings are significant in terms of the social and economic development of cities as well as their impact on the environment. Minimizing the consumption of natural resources in buildings has become an important goal for architects and urban planners. The search for sustainable urban development revealed the need to implement mechanisms that encourage the rational use of resources and the occupation of available spaces with minimal impact on the environment. In this context, environmental certification systems for buildings appear as a potential mechanism for the insertion of sustainable practices in the daily life of cities, aiming at the sustainability of available natural resources. This article presents the impacts caused by the rapid growth of cities and their populations as well as the benefits provided by the implementation of environmental certification for buildings in the country. It is believed that the race for the development of certified buildings can assist in reducing the need for urban public infrastructure, by mitigating impacts and producing inputs at the source (energy and water, for example), with direct and beneficial consequences for the government, paving the way for future incorporation of criteria in municipal legislation.